HLX is a candidate gene for a pattern of anomalies associated with congenital diaphragmatic hernia, short bowel, and asplenia. Issue 11 (12th September 2017) - Farrell, Sandra A.; Sodhi, Sandi; Marshall, Christian R.; Guerin, Andrea; Slavotinek, Anne; Paton, Tara; Chong, Karen; Sirkin, Wilma L.; Scherer, Stephen W.; Bérubé‐Simard, Félix‐Antoine; Pilon, Nicolas
Abstract : Isolated congenital diaphragmatic hernia is often a sporadic event with a low recurrence risk. However, underlying genetic etiologies, such as chromosome anomalies or single gene disorders, are identified in a small number of individuals. We describe two fetuses with a unique pattern of multiple congenital anomalies, including diaphragmatic hernia, short bowel and asplenia, born to first‐cousin parents. Whole exome sequencing showed that both were homozygous for a missense variant, c.950A>C, predicting p.Asp317Ala, in the H.20‐Like Homeobox 1 ( HLX1 ) gene. HLX is a homeobox transcription factor gene which is relatively conserved across species. Hlx homozygous null mice have a short bowel and reduced muscle cells in the diaphragm, closely resembling the anomalies in the two fetuses and we therefore suggest that the HLX mutation in this family could explain the fetal findings.